Development of the mathematical model of the biotreatment process of water-soluble gaseous emissions - Bakharevа Anna; Shestopalov Oleksіi; Filenko, Olesya; Novozhylova, Tetiana; Kobilyansky, Boris (Eastern-European Journal of Enterprise Technologies, 2017)
In the experimental research, the kinetic characteristics of hydrogen sulfide, sulfur dioxide and ammonia biooxidation were determined. It was found that the hydrogen sulfide and sulfur dioxide oxidation rates varied from 12 mg/g of biomass per hour in the region of the minimum pollution concentrations to the maximum value of 40 mg/g·h. As for ammonia, the variation range was 1.5–5 mg/g·h, respectively. The analytical description of the dependence of the specific degradation rate of pollutants on their concentration was proposed. The obtained quantitative values and variation nature of the specific oxidation rate prove the technological possibility of using the trickle-bed bioreactor for treatment of water-solvable gaseous emissions. Based on the experimental research, the mathematical description of the non-stationary biooxidation process of water-soluble gaseous hydrogen sulfide, sulfur dioxide and ammonia was developed. The developed mathematical model is based on the mass balance in the trickling layer of the bioreactor in the course of absorption and biodegradation processes. The analytical dependencies consider the emergence of dynamic balance between the harmful matter arrival intensity and oxidation. The state of dynamic balance determines the boundary of the bioreactor efficiency. The results allow evidence-based calculations of the hydrogen sulfide, sulfur dioxide and ammonia biotreatment process in the trickle-bed bioreactor.